FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Sylvia, Ardheana Mega; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of audit committee effectiveness, company operating size, profitability, and auditors' reputation on audit report lag in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The variables used in this study are audit effectiveness, company operating dimensions, profitability, and auditors' reputation as independent variables and the audit report lag as the dependent variable.This study used a purposive sampling technique with specific criteria and obtained 291 samples. Multiple linear regression analysis is the analytical method used in this study.The test results indicate that profitability has a significant negative effect on audit report delays. The effectiveness of the audit committee and the auditor's reputation have no significant effect on the delay in the audit report. In addition, the size of the company's operations also has no significant effect.